Mechanical characterization and modeling of knitted textile implants with permanent set - Pierrat, Baptiste; Nováček, Vít; Avril, Stéphane; Turquier, Frédéric (Journal of the mechanical behavior of biomedical materials, 2021)
Textile-based implant (mesh) treatment is considered as a standard of care for abdominal wall hernia repair. Computational models and simulations have appeared as one of the most promising approach to investigate biomechanics related to hernia repair and to improve clinical outcomes. This paper presents a novel anisotropic hypo-elastoplastic constitutive model specifically established for surgical knitted textile implants. The major mechanical characteristics of these materials such as anisotropy and permanent set have been reproduced. For the first time ever, we report an extensive mechanical characterization of one of these meshes, including cyclic uniaxial tension, planar equibiaxial tension and plunger type testing. These tests highlight the complex mechanical behavior with strong nonlinearity, anisotropy and permanent set. The novel anisotropic hypo-elasto-plastic constitutive model has been identified based on the tensile experiments and validated successfully against the data of the plunger experiment. In the future, implementation of this characterization and modeling approach to additional surgical knitted textiles should be the direction to follow in order to develop clinical decision support software for abdominal wall repair.
Keywords: testování materiálů; Herniorrhaphy; Hernia, Ventral; chirurgické síťky; Knitted textile-based implant; lidé; protézy a implantáty; ventrální hernie; Materials Testing; Textiles; Constitutive modeling; Abdominal wall hernia; operace kýly; Surgical Mesh; Prostheses and Implants; textilie; Humans